1980
DOI: 10.1161/01.res.46.2.190
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of exercise-induced regional myocardial dysfunction by propranolol. Studies in a canine model of chronic coronary artery stenosis.

Abstract: SUMMARY In 10 dogs, we placed a Doppler flow probe, an ameroid constrictor, and a hydraulic cuff occluder around the left circumflex coronary artery (CA). Ultrasonic dimension gauges were implanted in control segments (CS) and ischemic segments (IS) of the left ventricle (LV). A microtransducer was used to measure LV pressure (LVP). Sixteen to 35 days later, when CA occlusion was nearly complete and collaterals had developed, the dogs were studied by telemetry during exercise, while running behind a van (8-11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…12 Furthermore, the degree to which shortening is impaired within any single segment may vary according to interventions that may modify ischemia. 13 Hence, in our investigation it is reasonable to consider that the ischemic zone was composed of segments demonstrating both severe and moderate impairment of contractile function during P1. During P2 segments that had previously demonstrated moderate impairment of systolic contractile function may have demonstrated more severe impairment.…”
Section: Resultsmentioning
confidence: 91%
“…12 Furthermore, the degree to which shortening is impaired within any single segment may vary according to interventions that may modify ischemia. 13 Hence, in our investigation it is reasonable to consider that the ischemic zone was composed of segments demonstrating both severe and moderate impairment of contractile function during P1. During P2 segments that had previously demonstrated moderate impairment of systolic contractile function may have demonstrated more severe impairment.…”
Section: Resultsmentioning
confidence: 91%
“…nifedipine, measurements were obtained immediately after 5-minute infusions at rest and separately during exercise to assure "maximal" drug effects. In this manner, the study could be completed in all patients within 28 hours, including a maximum 26 Despite the similar antiischemic effect of all three drugs, the underlying hemodynamic mechanisms were quite different. After nitroglycerin, left ventricular filling pressure, end-diastolic volume and diastolic blood pressure decreased significantly, implying that a reduction in preload and afterload were the predominant effects.8' 9 Afterload was reduced even more by the vasodilatory effect of nifedipine reflected in reductions of systemic vascular resistance, blood pressure and left ventricular filling pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Variable durations of dysfunction min) have been noted after exercise in studies using this model (14,15,18,19) and may reflect differences in exercise intensity and duration, and extent of collateral flow during and after exercise. Regional myocardial blood flow post-exercise was not measured in these studies, however, and therefore the functional abnormalities observed in the postexercise period might have reflected continued hypoperfusion of deeper myocardial layers and not persistent functional abnormalities resulting from previous exercise-induced ischemia.…”
Section: Discussionmentioning
confidence: 86%